2005
DOI: 10.1021/jo048146u
|View full text |Cite
|
Sign up to set email alerts
|

2-(Aminomethyl)-oxazolines:  Highly Modular Scaffolds for the Preparation of Novel Asymmetric Ligands

Abstract: Highly modular chiral 2-(aminoalkyl)oxazolines have been prepared from alpha-amino acids and 1,2-amino alcohols. The amine-functionalized oxazolines were employed as scaffolds in the preparation of a number of different ligands with potential denticities varying from 2 to 5. The obtained ligands were employed and evaluated in the ruthenium-catalyzed asymmetric transfer-hydrogenation of acetophenone and in the titanium-catalyzed addition of diethylzinc to aldehydes. In the latter process, enantioselectivity up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Finally, oxazoline catalysts 1 a-j were prepared by cyclization of the corresponding amides III in the presence of a catalytic amount of 4-dimethylaminopyridine (DMAP). [22] A single crystal of organocatalyst (S,S)-1 j obtained from dichloromethane/hexanes (1:2) was subjected to X-ray structure analysis [23] (Scheme 1). Characterization data are given in the Supporting Information, which proved useful for understanding the structures of intermediates involved in the Strecker reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, oxazoline catalysts 1 a-j were prepared by cyclization of the corresponding amides III in the presence of a catalytic amount of 4-dimethylaminopyridine (DMAP). [22] A single crystal of organocatalyst (S,S)-1 j obtained from dichloromethane/hexanes (1:2) was subjected to X-ray structure analysis [23] (Scheme 1). Characterization data are given in the Supporting Information, which proved useful for understanding the structures of intermediates involved in the Strecker reaction.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (CDCl 3 , 400 MHz): d = 1.26 (m,9 H;CH 3(ethyl) , CH 3(future oxa) ), 1.41 (s,6 H;CH 3(bridge) 5 H;CH (arom) ); 13 C { 1 H} NMR (CDCl 3 , 100 MHz): d = 23.7,23.8 (CH 3(bridge) ) 24.0, 24.5 (CH 3 ), 50.0 (C quat(bridge) ), 55.7 (C quat(methyl side) ), 55.9 (CH), 66.2 (CH 2(phenyl side) ), 69.6 (CH 2(methyl side) ), 126. 4,128.0,128.9 (CH (arom) 1-{(4 R)-4-Phenyloxazolin-2-yl}-1-(4,4-dimethyloxazolin-2-yl)-1-methylethane [22] (Ph-dm-BOX): SOCl 2 (0.80 mL, 10.9 mmol) was added dropwise to a cooled solution (0 8C) of N-{(R)-2-hydroxy-1-phenylethyl}-N'-(2-hydroxy-1,1-dimethylethyl)-dimethylmalonamide (737 mg, 2.29 mmol) in CH 2 Cl 2 (150 mL). The reaction mixture was stirred overnight at ambient temperature, cooled to 0 8C and quenched by addition of aqueous NaHCO 3 (65 mL).…”
Section: Methodsmentioning
confidence: 99%
“…[8] Inspired by the results obtained by Zhang, we investigated the catalytic ability of a number of ruthenium complexes based on N-functionalized 2-aminomethyloxazoline derivatives. [9] The results were rather poor, but interestingly we found that a Boc-protected amino acid hydroxy-amide, a precursor to the 2-aminomethyloxazolines, acted as an efficient ligand in the transfer hydrogenation. The combination of [RuCl 2 A C H T U N G T R E N N U N G (p-cymene)] 2 and ligands 1 or 2 generated ruthenium complexes which catalyzed the reduction of aryl alkyl ketones in good yield and in excellent enantioselectivity.…”
Section: Introductionmentioning
confidence: 93%